Program "believing in me" to improve the self-esteem of the students of the rst grade of elementary of the educational institution Nro 32011 "Hermilio Valdizán", Huánuco 2017 - Acosta-Malpartida, Katya I. (2019)
The present investigation had the purpose of determining the level of influence of the "BELIEVE IN ME" Program, in the improvement of the self-esteem of the first grade students of the Educational Institution Nº 32011 Hermilio Valdizán, Huánuco-2017. The research is experimental with a quasi-experimental design with two groups. The population constituted the students of the 1st Grade of Primary enrolled and the sample conformed by the sections C and D that they added 48 students. The instrument used for the data collection was a self-esteem test. The results of the present research indicate that the "BELIEVE IN ME" Program significantly influences the improvement of the self-esteem of the first grade students of the Educational Institution Nº 32011 Hermilio Valdizán, Huánuco-2017, since before applying said program the students had on average an unsuitable assertiveness with 12.04 points out of a total of 20; whereas after applying the indicated program the students on average had an adequate assertiveness with 17.29 points. The same happened with the dimensions of assertiveness such as behavior, physical appearance and attributes, anxiety and happiness and satisfaction that after applying the program students went from an inadequate, average or regular assessment to an appropriate or high assessment.